2022
DOI: 10.3390/min12091153
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Properties of the Copper Slags from the SarCheshmeh Smelter Plant, Iran, in View of Value Recovery

Abstract: Annually, hundreds of thousands of tons of slags are involved in the reverberator and flash smelting as well as converting operations of Cu-Fe sulfide concentrates to produce matte in the Sar Cheshmeh copper smelter plant, Iran, disposed in the landfill and cooled in air. Due to their relatively high average copper content (about 1.5 wt%), a mineral processing plant based on the flotation process has recently been established to produce thousands of tons of Cu-sulfide concentrate after slag crushing and fine g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Consequentially, the use of binder based on ordinary cement is impossible. Experiments on the creation of hardening materials based on waste from potash ore processing have shown the advantage of magnesium binders [74,75], so the use of magnesium-containing components as a binder could be an acceptable option.…”
Section: Backfill Componentsmentioning
confidence: 99%
“…Consequentially, the use of binder based on ordinary cement is impossible. Experiments on the creation of hardening materials based on waste from potash ore processing have shown the advantage of magnesium binders [74,75], so the use of magnesium-containing components as a binder could be an acceptable option.…”
Section: Backfill Componentsmentioning
confidence: 99%
“…It is sufficient to consider the risks from the presence of hazardous components in industrial waste and the likelihood of their spread and impact. Such risks are noticeably reduced when the harmful effects are neutralized by reducing hazardous elements in industrial waste [7] or mined-out gas [40,41] to zero.…”
Section: 𝐸 ∑ ∑ 𝐶 ∑ 𝐶 𝑄 mentioning
confidence: 99%
“…Increasing the efficiency of metal extraction from processing wastes [1,2], metallurgical slags [3,4] or wastewater from mines and concentrating plants [5] is closely related to environmental [6] and economic [7] problems. The solution to these problems is associated with aspects of the transformation of mining and processing waste by reducing the heavy metal content to zero [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another study evaluated different metallurgical materials and processes including the production of copper and tin bronze objects from the Middle Elamite site of Haft Tappeh (Oudbashi & Mishmastnehi, 2020). Mohamadi Nasab et al (2022) also suggested the highest rate of copper recovery from the crystallized slags containing moderate to coarse copper‐bearing particles by the flotation process. However, the potential environmental burdens of slag, unwanted minerals, and released gases and wastewater are unknown.…”
Section: Introductionmentioning
confidence: 98%